The Feasibility of Thoracoscopic Resection in Bronchiectasis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2017)
Introduction:Minimally invasive surgery is the treatment of choice in early-stage lung cancer. However, experience in infectious lung disease, primarily bronchiectasis, is limited probably because of the presence of dense pleural adhesions, multiple lymph nodes, and spiral bronchial arteries. The present study shows our experience of video-assisted thoracoscopic surgery (VATS) lobectomy and segmentectomy in the treatment of bronchiectasis.Materials and Methods:Patients who underwent VATS lobectomy or segmentectomy in our clinic between April 2008 and 2015 were retrospectively evaluated. Surgery was indicated in patients with radiologic localized bronchiectasis who also had a history of recurrent lower respiratory tract infection or expectorating mucopurulent secretion. The patients were analyzed in terms of age, sex, thoracotomy conversion rate, postoperative drainage amount, chest tube removal time, length of hospital stay, morbidity, and mortality.Results:A total of 44 patients initially underwent VATS pulmonary anatomic resection and 41 procedures were completed on 40 patients. One patient had bilateral resection. Fifteen patients were male individuals and 26 were female individuals. The average age was 31.4 (15 to 57) years. Forty lobectomies and 1 segmentectomy were performed. The conversion rate was 6.8%. VATS was performed on 28 patients by 3 ports, 8 patients by 2 ports, and 5 patients by a single port. In terms of anatomic resections, 18 patients underwent left lower lobectomy, 8 right lower lobectomy, 8 middle lobectomy, 6 right upper lobectomy, and 1 patient underwent lingular segmentectomy. No major postoperative complication or mortality was observed. Prolonged air leak was observed in 2 patients and subcutaneous emphysema occurred in 2 patients. The average postoperative drainage amount, chest tube removal time, and length of hospital stay were 320 mL, 3.1 (1 to 11) days, and 4.6 (2 to 11) days, respectively.Conclusions:VATS pulmonary resection is a safe, feasible, and effective treatment in the surgery of bronchiectasis with low morbidity and mortality rates. Moreover, because of cosmetic results, patients with benign diseases such as bronchiectasis could be initiated by minimally invasive surgery options just like patients with malignancies.
Keywords: bronchiectasis; lobectomy; segmentectomy; videothoracoscopy; ASSISTED THORACIC-SURGERY; CELL LUNG-CANCER; QUALITY-OF-LIFE; SINGLE-CENTER; LOBECTOMY; THORACOTOMY